Sustainability Management Program for Industries- A Case Study - Alwin, Long Su Weng; Atnaw, Samson M.; Roziah, Zailan; Muhamad Muhtazam, Noor Din (EDP Sciences, 2017)
This research studied the effectiveness of Sustainability Management Program in improving production efficiency of the manufacturing site with verified result using the regression analysis. For this study, a dairy manufacturing industry located in Malaysia was selected and major energy consuming equipment in the industry plant were identified. Sustainability Management Program (SMP) was carried out for three years and energy consumption and product has improved regression coefficients of 0.625 in 2013, 0.826 in 2014, and 0.878 in 2015 as the manufacturing site becomes more energy efficient. This suggests that the energy management should be carried out in a continuous manner with energy management team responsible for energy saving practices.